Maoist "Spring Thunder" the Naxalite movement 1967-1972 - Mukherjee, Arun 1933- (Kolkata K.P. Bagchi & Co., 2007)
Chiefly with reference to Naxalbari and Calcutta, India.
Includes bibliographical references and index.
In English
Keywords: Naxalite movement -- India -- Naxalbari -- History -- 20th century; Naxalite movement -- India -- Kolkata -- History -- 20th century; Naxalbari (India) -- Politics and government -- 20th century; Kolkata (India) -- Politics and government -- 20th century